Difference between revisions of "TrigSimplify Command"

From GeoGebra Manual
Jump to: navigation, search
m (style: bulletted list)
Line 1: Line 1:
<noinclude>{{Manual Page|version=4.2}}</noinclude>{{betamanual|version=4.2}}
+
<noinclude>{{Manual Page|version=4.2}}</noinclude>
 
{{command|cas=true|function}}
 
{{command|cas=true|function}}
 
;TrigSimplify[ <Expression> ]
 
;TrigSimplify[ <Expression> ]
Line 6: Line 6:
 
:*<code>TrigSimplify[1 - sin(x)^2]</code> gives ''-sin²(x)+1''.
 
:*<code>TrigSimplify[1 - sin(x)^2]</code> gives ''-sin²(x)+1''.
 
:*<code>TrigSimplify[sin(x)^2 - cos(x)^2 + 1]</code> gives ''2 sin²(x)''.</div>}}
 
:*<code>TrigSimplify[sin(x)^2 - cos(x)^2 + 1]</code> gives ''2 sin²(x)''.</div>}}
 +
 
==CAS Syntax==
 
==CAS Syntax==
 
;TrigSimplify[ <Expression> ]
 
;TrigSimplify[ <Expression> ]
Line 12: Line 13:
 
:*<code>TrigSimplify[1 - sin(x)^2]</code> gives ''cos²(x)''
 
:*<code>TrigSimplify[1 - sin(x)^2]</code> gives ''cos²(x)''
 
:*<code>TrigSimplify[sin(x)^2 - cos(x)^2 + 1]</code> gives ''2 sin²(x)''.</div>}}
 
:*<code>TrigSimplify[sin(x)^2 - cos(x)^2 + 1]</code> gives ''2 sin²(x)''.</div>}}
 +
 
{{note|1=<div>  
 
{{note|1=<div>  
 
:* This command works for the variable ''x'' only! (<code>TrigSimplify[1 - sin(y)^2]</code> gives ''-sin²(y) + 1''.)
 
:* This command works for the variable ''x'' only! (<code>TrigSimplify[1 - sin(y)^2]</code> gives ''-sin²(y) + 1''.)
 
:* See also [[TrigExpand Command]] and [[TrigCombine Command]].</div>}}
 
:* See also [[TrigExpand Command]] and [[TrigCombine Command]].</div>}}

Revision as of 11:41, 21 December 2012



TrigSimplify[ <Expression> ]
Simplifies the given trigonometric Expression.
Examples:
  • TrigSimplify[1 - sin(x)^2] gives -sin²(x)+1.
  • TrigSimplify[sin(x)^2 - cos(x)^2 + 1] gives 2 sin²(x).


CAS Syntax

TrigSimplify[ <Expression> ]
Simplifies the given trigonometric Expression.
Examples:
  • TrigSimplify[1 - sin(x)^2] gives cos²(x)
  • TrigSimplify[sin(x)^2 - cos(x)^2 + 1] gives 2 sin²(x).


Note:
© 2021 International GeoGebra Institute